The Book of Dirt - Presser, Bram; Text Publishing (Melbourne, Victoria : The Text Publishing Company, 2017)
'An immense work of love and anger, a book Bram Presser was born to write.' Joan London They chose not to speak and now they are gone...What's left to fill the silence is no longer theirs. This is my story, woven from the threads of rumour and legend. Jakub Rand flees his village for Prague, only to find himself trapped by the Nazi occupation. Deported to the Theresienstadt concentration camp, he is forced to sort through Jewish books for a so-called Museum of the Extinct Race. Hidden among the rare texts is a tattered prayer book, hollow inside, containing a small pile of dirt. Back in the city, Františka Roubíčková picks over the embers of her failed marriage, despairing of her conversion to Judaism. When the Nazis summon her two eldest daughters for transport, she must sacrifice everything to save the girls from certain death. Decades later, Bram Presser embarks on a quest to find the truth behind the stories his family built around these remarkable survivors. The Book of Dirt is a completely original novel about love, family secrets, and Jewish myths. And it is a heart-warming story about a grandson's devotion to the power of storytelling and his family's legacy.
General.
Keywords: 1939-1945; Biographical fiction; Holocaust survivors -- Europe -- Biography -- Fiction; Holocaust survivors -- Europe -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Jewish families -- Biography -- Fiction; Jewish families -- Fiction; Jews -- Europe -- Biography -- Fiction; Jews -- Europe -- Fiction; Biographical fiction; Fiction - General; Fiction / Jewish; Fiction: general & literary; Holocaust survivors; Jewish families; Jews; Modern & contemporary fiction (post c 1945); Europe; Australian; Electronic books; Electronic books; Biographical fiction